2018
DOI: 10.1097/md.0000000000013301
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of tumor-infiltrating lymphocytes in hepatocellular carcinoma

Abstract: Background:In patients with hepatocellular carcinoma (HCC), the prognostic role of tumor-infiltrating lymphocytes (TILs) for survival is still controversial. A meta-analysis was performed to investigate the prognostic effect of TILs in HCC.Methods:We identify studies from PubMed, Embase, and the Cochrane Library to evaluate the prognostic value of TILs in patients with HCC. A meta-analysis was conducted to estimate overall survival and disease-free survival. The hazard ratio (HR) and 95% confidence interval (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 58 publications
(133 reference statements)
7
65
0
Order By: Relevance
“…On the contrary, high density of CD3 + TILs was related to better PFS after excluding the study which contributed to the high inner heterogeneity. The similar conclusion was also drawn by Ding et al in hepatocellular carcinoma 27 . And the mechanisms were not exactly explained in previous study, which needs to be answered in the future.…”
Section: Discussionsupporting
confidence: 89%
“…On the contrary, high density of CD3 + TILs was related to better PFS after excluding the study which contributed to the high inner heterogeneity. The similar conclusion was also drawn by Ding et al in hepatocellular carcinoma 27 . And the mechanisms were not exactly explained in previous study, which needs to be answered in the future.…”
Section: Discussionsupporting
confidence: 89%
“…It has been long time recognised that increased Tlymphocyte infiltrate is associated with improved overall and progression free survival in HCC [29]. However, despite T-cell infiltration tumours ultimately progress and metastasise as a result of the 'exhaustion' of proinflammatory T-cell populations and accumulation of regulatory T-lymphocytes [30][31][32].…”
Section: T-cellsmentioning
confidence: 99%
“…TME comprises a mass of heterogeneous cell types, including tumor-in ltrating lymphocytes (TILs), endothelial cells, cancer stem cells, and broblasts, alongside cancer cells. Previous studies have shown that the ratio of TILs play a crucial role in the treatment and prognosis of various tumors, [28][29][30] including MIBC. [31] The TIL compartment could even service as a classi cation in triple negative breast cancer.…”
Section: Discussionmentioning
confidence: 99%